Analisis Sistem Antrean pada Customer Service Representative (CSR) Plasa Telkom Cilacap menggunakan Model Multi Channel Single Phase - Setiawati, Desti; Hartono, Bryan Pudji; Ahmad, Mizan (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2024)
Plasa Telkom Cilacap is one of the branch offices of PT. Telekomunikasi Indonesia Tbk. (Telkom) engaged in information and communication technology (ICT) services and telecommunication networks in Indonesia. Plasa Telkom Cilacap plays a crucial role in fulfilling customer service needs. With the increasing number of customers who want to serve immediately, it is worrying that it will cause long queues, causing Customer Service Representative (CSR) services to customer needs to be not optimal. This study analyzed the queuing system at Plasa Telkom Cilacap using a queuing system analysis based on queuing performance and costs to know the optimal number of CSR needed at Plasa Telkom Cilacap. At the moment, Plasa Telkom Cilacap uses the Multi-Channel Single Phase queuing model with 3 CSRs. The data used in this study are the number of arrivals, length of service, and salary data. Based on the result, the optimal number of CSRs is 2 CSRs.